“Please, bring me some coffee”: Illegitimate tasks as the explanation for the relationship between organisational sexism and occupational well-being // Inklusion und Intersektionalität in institutionellen Bildungskontexten - García Johnson, Carolina Pía; Otto, Kathleen (My University, 2020)
While overt forms of sexism in organisations are on the decline, covert ones are becoming the norm. This article argues that illegitimate tasks are a disguised form of gender-based discrimination and harassment. To support this argument, evidence is provided about the effects of sexism on occupational well-being that are caused by undertaking illegitimate tasks. The authors focus on the relationship between sexist organisational climate and illegitimate tasks and the resulting effects on job satisfaction and irritation. The empirical data used in the analyses were obtained from a cross-sectional study of a sample of German psychologists. After controlling for the effects of gender, the results provided evidence of the negative effects that a sexist organisational climate has on irritation and job satisfaction, mediated by illegitimate tasks.
Keywords: Arbeit; human resources; illegitimate tasks; irritation; job satisfaction; occupational well-being; Sexismus; sexist organisational climate; ddc:303